Implementasi Program Merdeka Belajar Menuju Era Society 5.0 - Novita Cahyani, Rachmalia; Aulia Zahro, Aisyah; Arrizal Afifuddin, Achmad (Institut Riset dan Pengembangan Indonesia, 2022)
Society 5.0 is an era that combines the concept of a human-centered technology-based society advocated by the Japanese government. In this era, the community, especially students, need to improve their soft skills in order to improve their skills and learning skills so that they can become capital to become a more skilled workforce in the future. Students and students face changes due to current technological developments. Therefore, the Minister of Education and Culture of the Republic of Indonesia, Nadiem Makarim, organized a study program with the concept of Merdeka Education, a concept that was initiated to give students the freedom to think critically and intellectually. In this article, we will try to consider what the implementation of independent learning in high schools and universities in Indonesia will look like in the Society 5.0 era. The writing of this article uses a literature study by reviewing several journals that are relevant to the topics discussed qualitatively. The results of the study in this article show that the implementation of the independent learning curriculum is related to society in the 5.0 era. The capabilities that must be possessed are creativity and innovation so that they become strong, skilled and tenacious human resources. The implementation of independent learning is carried out with careful planning that can improve the quality of Indonesian education and can prepare graduates who excel and are able to compete globally.